Fisheries Science - Maita, Masashi; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer.)
Fisheries Science is the official journal of the Japanese Society of Fisheries Science, which was established in 1932. Recognized as a leading journal in its field, Fisheries Science is respected internationally for the publication of basic and applied research articles in a broad range of subject areas relevant to fisheries science. All articles are peer-reviewed by at least two experts in the field of the submitted paper. Published six times per year, Fisheries Science includes about 120 articles per volume. It has a rich history of publishing quality papers in fisheries, biology, aquaculture, environment, chemistry and biochemistry, food science and technology, and Social Science.
Keywords: Food -- Biotechnology; Aquatic ecology; Wildlife; Fish; Fish & Wildlife Biology & Management; Freshwater & Marine Ecology; Food Science